Immunomodulatory Effects of Aqueous Extracts of Auricularia sp and Pleurotus sp Mushrooms in Cyclophosphamide- Immunosuppressed Wistar Rats - Kyakulaga, A. H.; Ogwang, P. E.; Obua, C.; Nakabonge, G.; Mwavu, E. N. (British Journal of Pharmaceutical Research, 2013)
To determine the immunomodulatory effect of aqueous extracts of Auricularia sp and Pleurotus sp mushrooms using an immunosuppression animal model. Study Design: Pre-clinical experimental study. Place and Duration of Study: Department of Pharmacology and Therapeutics, College of Health Sciences and Division of Pharmacology, Department of Physiological Sciences, School of Veterinary Medicine, Makerere University, between August 2010 and December 2011. Methodology: A total of 80 Wistar rats divided into 8 groups (n=10) were used in the experimental study. Cyclophosphamide (10mg/kg) was administered orally (p.o) to fifty (50) Wistar rats in the first 5 groups for 28 days. In addition, rats in Group I received distilled water, groups II & III received 300mg/kg & 600mgkg of Auricularia sp extract respectively and Groups IV &V received 400mg/kg & 800mg/kg Pleurotus sp extract respectively. Wistar rats in Group VI received only 300mg/kg Auricularia sp extract, group VII received 400mg/kg Pleurotus sp extract and Group VIII received only distilled water. Blood samples were collected on days 0, 14 and 28 to determine the total and differential WBC counts. Data is presented as mean±SEM and analyzed using one-way ANOVA followed by a student’s t-test for statistical significance. Mean values are compared with initial values and the control group (Group VIII). Results: No mortality of Wistar rats was observed over the 28-day experimental period. Cyclophosphamide though caused statistically significant (p<0.05) reduction in total WBC on day 14 and 28 compared with day 0 in control group from 11.26±0.59 on day 0 to 6.11±0.41 day 14, & 4.12±0.22 on day 28. Lymphocytes and Neutrophil counts were also significantly reduced in control group by day 28 compared to mushroom extract treated rats. Results show that aqueous extracts of Auricularia sp & Pleurotus sp mushrooms significantly (p<0.05) moderated the reductions in total & differential WBC on day 14 and 28 as compared to the control group. The mushroom extracts also increased total and differential WBC in normal rats as compared to the normal group (Group VIII). Conclusion: Aqueous extracts of Auricularia sp and Pleurotus sp mushrooms moderated cyclophosphamide-induced reduction in WBC in Wistar rats indicating potential benefit in chemotherapy induced immunosuppression. Application of these mushrooms in immune suppression research appears to be new as reflected in the literature. These are however preliminary data to be more completely documented by further experiments, possibly investigating also some aspect of immune cell functions (e.g. cytotoxicity or cytokine production).
Keywords: Immunomodulatory; Aqueous extract; Immunosuppression; Wistar rats; Wild edible mushrooms.